2006
DOI: 10.1002/mar.20111
|View full text |Cite
|
Sign up to set email alerts
|

Literal versus extended symbolic messages and advertising effectiveness: The moderating role of need for cognition

Abstract: The authors classify an advertisement as an extended symbolic message (ESM) when the ad's subject and message are presented in a nonliteral format. The study compares the advertising effectiveness of the ESM with that of a literally equivalent message (LEM) when the ESM contains either a salient cue (Experiment 1) or subtle cue (Experiment 2) to a nonliteral interpretation. The results indicate that the audience's need for cognition moderates the effectiveness of the ESM. In comparison with an LEM, exposure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 44 publications
(46 reference statements)
1
40
0
1
Order By: Relevance
“…It is well known that ad recipients exert cognitive effort only when they are motivated and able to do so. For example, Brennan and Bahn (2006) observed that when study participants viewed ads that required recipients to infer the subject of a verbal comparison and identify several points of comparison, participants who lacked motivation failed to "put forth the cognitive effort required to unravel the brand claims" (p. 277). Based on this and many other findings suggesting that motivation is a necessary antecedent of cognitive effort, it can be expected that consumers at the very lowest levels of motivation who view an advertisement will not devote sufficient cognitive effort to interpret the meaning of nonverbal symbolic signs and metaphors.…”
Section: Interpreting the Meaning Of Nonverbal Advertising Elementsmentioning
confidence: 96%
See 2 more Smart Citations
“…It is well known that ad recipients exert cognitive effort only when they are motivated and able to do so. For example, Brennan and Bahn (2006) observed that when study participants viewed ads that required recipients to infer the subject of a verbal comparison and identify several points of comparison, participants who lacked motivation failed to "put forth the cognitive effort required to unravel the brand claims" (p. 277). Based on this and many other findings suggesting that motivation is a necessary antecedent of cognitive effort, it can be expected that consumers at the very lowest levels of motivation who view an advertisement will not devote sufficient cognitive effort to interpret the meaning of nonverbal symbolic signs and metaphors.…”
Section: Interpreting the Meaning Of Nonverbal Advertising Elementsmentioning
confidence: 96%
“…Researchers (e.g., Brennan & Bahn, 2006;Phillips, 1997) have also suggested that real-life advertisers might intentionally create metaphors that are difficult for ad recipients to interpret. Such metaphors are not the focus of the current research.…”
Section: Stimuli Creationmentioning
confidence: 97%
See 1 more Smart Citation
“…Zo laat experimenteel onderzoek naar tropen in het algemeen zien, dat tropen vooral effectief zijn bij lezers met een hoge neiging tot nadenken: deze lezers vinden het namelijk leuk om puzzels op te lossen. Bij lezers met een lage neiging tot nadenken zijn tropen veel minder effectief (Brennan & Bahn, 2006). Onderzoek naar de rol van NFC bij de effectiviteit van humor laat juist een tegengesteld patroon zien: Humor is effectiever bij lezers met een lage NFC dan bij lezers met een hoge NFC (Zhang, 1996).…”
Section: Kenmerken Van De Ontvangerunclassified
“…Additional research found that individuals with a high need for cognition (cognitive processors), as opposed to a low need for cognition, preferred verbal information (Martin et al, 2005;Sojka and Giese, 2001;Venkatraman et al, 1990) and enjoyed the problem-solving challenge presented in verbal symbolism (Brennan and Bahn, 2006). NFC individuals' preference for verbal stimuli should reflect a higher level of attitude towards the web page than would be expressed by those low in cognition.…”
Section: Information Processing Stylesmentioning
confidence: 99%